(untitled) (Research, Society and Development, 2021)
The present work aimed to elaborate smoked sausages using raw material from different animal species (Tilapia, bovine, swine and poultry) and to analyze their chemical, microbiological and sensory characteristics. Four types of sausages were made: one of them from filleting residues (cut in “V” of the fillet) of tilapia, poultry breast, pork ham and beef. The data obtained in the different analyzes were subjected to analysis of variance (ANOVA) and Tukey’s test at 5% significance was applied. Significant difference was observed for all analyzed nutrients. The sausage based on fish chips had a caloric value (67.14 kcal/100g) and low levels of lipids (4.21%), protein (15.52%) and high moisture contents (66.84%) and minerals (3.80%), when compared to the other sausages, but a filleting residue was used and not the noble part of the fish meat (fillet). Based on the sensory analysis, the tilapia shavings sausage obtained a good evaluation in terms of color, aroma, flavor and texture, showing good acceptance by consumers. All sausages were within the standards required by law, therefore suitable to be consumed.